Activity-Based Intelligence prevedere il futuro osservando il presente con gli strumenti Hexagon Geospatial - Zotti, Massimo (GEOmedia, 2015)
The intelligence of human activities on the earth's surface, obtained through the analysis of earth observation data and other geospatial information, is vital for the planning and execution of any military action, for peacekeeping or for humanitarian emergencies. The success of these actions largely depends on the ability to analyze timely data from multiple sources. However, the proliferation of new sources of intelligence in a Geospatial big data scenario increasingly complicate the analysis of such activities by human analysts. Modern technologies solve these problems by enabling the Activity Based Intelligence, a methodology that improves the efficiency and timeliness of intelligence through the analysis of historical, current and future activity, to identify patterns, trends and relationships hidden in large data collections from different sources.